(3GdEMGWI aj JGQjN ZQfGWIs - (3eMeO Hf YHO Gddg Hf SYjO GdSdeGfj GddhTj GdCUd, GdZQfGWj GdCfOdSj, CHh YHO Gddg, GdTgjQ HdSGf GdOjf GHf GdNWjH,J (B776 (3g` s
(3ChdgG (B:s
(3JHOC ef (B" (3GdebQFjf(B" (3HJQLeI (B: (3ehSi Hf YHO GdQMef Hf jMji GdYQHi GddNei , bhdg (B: (3ef Cgd hjYQa HGdfaMGJ fMhi dZhi ef ZQfGWI , hCNP GdfGS Yfg cKjQkG eTjNJg (B: (3Qhi Yf CHj GdbGSe s
(3BNQgG (B:s
(3ef JQLeI YHO GdhOhO Hf YHO GdQMef Hf Ydi Hf YHO Gdedc , bhdg (B: (3CHh eMeO Ldjd eTjNJg(B: (3CNP Yf ef Qhi Yfg (B: (3Qhi Yfg GHfg GdbGVi CHh GdbGSe CMeO haGJg(B: (3Jhai SfI GKfJjf hNeSjf hNeS eFI ? Je gPG GdSaQ HMeO Gddg s
(3LRA efgs
(3JeJ fSGNJgG ai TgQ QeVGfs
(3ChQGbgG eVWQHI GdJQJjH HCWQGagG WeSs
(3ai GdeYgO fSNI CNQi HQbe (B1339 (3JGQjN s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
Keywords: (3GdJGQjNs